Ocular surface ophthalmoheliosis in a region of Patagonia - Suarez, Maria Fernanda (2019)
The aim of this mini review is to describe the prevalence of Environmental Proteinaceous Corneal Degeneration (EPCD), pinguecula and pterygium and the association among them. We performed a transversal/observational study in individuals living all their lives in the El Cuy Department, province of Río Negro in the Argentinean Patagonia. The patients investigated were consecutive non-probabilistic. The prevalence of ophthalmoheliosis was 34% of pinguecula, followed by 30% of EPCD and 12% of pterygium. A statistically significant association was found between EPCD and male patients (p <0.05). There was association between EPCD with pinguecula and with pterygium, both more frequent in males (p <0.05). Our investigation shows important prevalence of EPCD, pinguecula and pterygium in individuals that live at this region of the Argentine Patagonia. As far as we know, this is the first work in the world that shows coexistences between these three ophthalmoheliosis.